First report on clinical and radiological features of COVID-19 pneumonitis in a Caucasian population: Factors predicting fibrotic evolution - Marvisi, Maurizio (Int J Infect Dis, 2020)
BACKGROUND: At the end of February, the Lombardy region (Northern Italy) was involved in the pandemic spread of the new COVID-19. We here summarize the clinical and radiological characteristics of 90 confirmed cases and analyze their role in predicting the evolution of fibrosis. METHODS: We retrospectively analyzed the clinical and radiological data of 90 patients with COVID-19 pneumonitis. All subjects underwent an HRCT study on the day of admission and eight weeks later, and were treated with lopinavir + ritonavir (Kaletra) 400/100 mg two times a day or darunavir + ritonavir two times a day, and Hydroxychloroquine 200 mg two times a day. Pulmonary fibrosis was defined according to the Fleischner Society glossary of terms for thoracic imaging. RESULTS: Twenty-three patients developed pulmonary fibrosis (25.5%): 15 were males, whose mean age was 75 ± 15. The majority were active smokers (60.8%) and had comorbidities (78.2%), above all, hypertension (47.8%), and diabetes (34.7%). Interestingly, in our series of cases, the "reversed halo sign" is frequent (63%) and seems to be a typical COVID-19 pneumonitis pattern. The patients showing fibrosis had a higher grade of systemic inflammation (ESR and PCR) and appeared to have bone marrow inhibition with a significant reduction in platelets, leukocytes, and hemoglobin. CONCLUSIONS: To conclude, our data showed that the reversed halo sign associated with a ground-glass pattern may be a typical HRCT pattern of COVID-19 pneumonitis. The evolution to pulmonary fibrosis is frequent in older males and patients with comorbidities and bone marrow involvement.